Quality of work life in occupational safety and health among Malaysian workers in different industries in Malaysia - Mazlan, Safiah Rohaizah; Md Tamrin, Shamsul Bahri; Ng, Yee Guan; Vivien, How; Ab Rahman, Rozanah; Basri, Johari; Zerguine, Haroun; Mohd Suadi Nata, Dayana Hazwani; Shariat, Ardalan (Universiti Putra Malaysia, 2018)
Background: Quality of Work Life (QWL) is a subset of the quality of life which expresses the interactions between workers and their total working environment with individual or human dimension. Objectives: The objective of this study was to determine the prevalence of QWL among Malaysian workers. Methods: 2740 respondents (1921 males and 819 females) were randomly selected from 11 different industries from all states of Malaysia. Respondents were aged between 18 to more than 55 years and were a local OSH Personnel and local general workers. Face to face interviews were conducted in all the selected industries using a structured questionnaire form adapted from Malay-sian OSH Profile 2016. Respondents have completed the questionnaire under instructions and supervision of the research team. Results: Majority of the respondents were male (70.1%) and from manufacturing industries (76.3%). 50% of the respondents identified a high level of QWL in each component like not having a stress with the work load (85.5%), good work environment (78.4%), family life (83.1% and 83.6%), enough income and distribution (58.9%), good communication and harmonies relationship between colleagues and boss (93.4% and 88.7%), good facilities (88.6%), welfare at work (71.3%) and productive working condition (80.8%). There is a significant difference between QWL and type of industries [F(10)=12.897, p=0.001] where agriculture industry had the highest QWL. There is significant difference between QWL and gender (p=0.009) where male reported higher QWL compared to female. Conclusion: These findings could be used by the organizations in order to enhance its performance, productivity, employees' commitment and satisfaction.